The poetry of place : lyric, landscape, and ideology in Renaissance France - Mackenzie, Louisa, 1970- (European Union studies., 2011)
The sixteenth century in France was marked by religious warfare and shifting political and physical landscapes. Between 1549 and 1584, however, the Pleiade poets, including Pierre de Ronsard, Joachim Du Bellay, Remy Belleau, and Antoine de Baif, produced some of the most abiding and irenic depictions of rural French landscapes ever written. In The Poetry of Place, Louisa Mackenzie reveals and analyses the cultural history of French paysage through her study of lyric poetry and its connections with landscape painting, cartography, and land-use history.